Upaya Mentradisikan Kitab Gundul (Turāth) Sebagai Warisan Ulama Nusantara Melalui Metode Pembimbingan Di Pondok Modern Darul Hikmah, Tulungagung - Khaer, Misbakhul (Prodi Tasawuf dan Psikoterapi Fakultas Usluhuddin dan Dakwah IAIN Kediri, 2020)
The orientation of pesantren education should be projected to shape people having a high awareness that the characteristics of Islamic teachings are Syumuli (holistic). So the products are also expected to have sufficient capability to meet the challenges and demands of life anytime and anywhere. Based on this premise, Darul Hikmah as the only modernity-based institution in Tulungagung Regency tried to do tajdid (renewal) in its education system by adopting two traditions of the Salaf pesantren; recitation of the bandongan and sorogan system. This tradition is considered as the wealth and excellence of traditional pesantren which aims to produce prospective scholars who are able to take part in the community and able to respond to religious issues. Therefore, it is necessary for the writer to conduct a research as well as guidance to find out the extent of the Darul Hikmah Islamic Boarding School Institute in implementing the two traditions and how the results of the application are. The temporary results of this guidance are satisfactory. This was proven by the enthusiasm of the students and students who never tired to continue to follow this program. From the institution also strongly supports this guidance program so that it includes it as an extra-curricular activity that must be tested at the time of graduation of students. In addition, the institution also added more classical books to be used as reference material and comparison for the books being studied. Although there are a number of things that hamper our program, such as the different abilities of students in capturing the guidance of the learning of the yellow book, the lack of habituation to the study of the yellow book, and others. We hope this program will continue to develop even better, and have a positive effect so that it can improve the achievements of the students and enrich their Islamic knowledge.